2006
DOI: 10.1111/j.1742-7843.2006.pto_560.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Food Flavour Cinnamaldehyde on the Antioxidant Status of Rat Kidney

Abstract: Cinnamaldehyde, a food flavour, has a high potential for human consumption in India. In this study, we evaluated the effect of cinnamaldehyde on the antioxidant status of the rat kidney. Rats were given cinnamaldehyde orally by gavage at dose levels of 2.14, 6.96, 22.62 and 73.5 mg/kg body weight/day for the period of 10, 30 and 90 days. The non-enzymatic antioxidants ascorbic acid, a-tocopherol and reduced glutathione were decreased while the antioxidant enzymes, superoxide dismutase, glutathione peroxidase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…For example, carnosic acid as the major phenolic constituent of rosemary leaves exhibits potent antioxidant activity often stronger than some synthetic antioxidants (Charles, 2013). Additionally, the main bioactive compounds of cinnamon bark (cinnamaldehyde; Gowder et al, 2006), clove bud (eugenol and gallic acid; Kramer et al, 1985), and turmeric (curcumin and other curcuminoids; Aftab and Vieira, 2010) as well as their raw extracts are known to exhibit strong lipophilic and hydrophilic antioxidant properties (Wu et al, 2004). Also, synergism among herbal combinations has been observed (Aftab and Vieira, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…For example, carnosic acid as the major phenolic constituent of rosemary leaves exhibits potent antioxidant activity often stronger than some synthetic antioxidants (Charles, 2013). Additionally, the main bioactive compounds of cinnamon bark (cinnamaldehyde; Gowder et al, 2006), clove bud (eugenol and gallic acid; Kramer et al, 1985), and turmeric (curcumin and other curcuminoids; Aftab and Vieira, 2010) as well as their raw extracts are known to exhibit strong lipophilic and hydrophilic antioxidant properties (Wu et al, 2004). Also, synergism among herbal combinations has been observed (Aftab and Vieira, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have addressed to evaluate the anti-inflammatory, antibacterial and antioxidant effects of cinnamaldehyde. Reduction in the production of prostaglandin E2 and inhibition of cyclooxygenase-2 (COX-2) expression and subsequent significant decrease in Interleukin-1ß [19], increase in glutathione peroxidase activity [20], and bactericidal activity against Streptococcus [21] and Staphylococcus species, lactobacilli [17], and other gram positive and negative bacteria [22] are the results brought about as the effect of cinnamaldehyde. Clinical findings of the present study showed a significantly delayed onset of mucositis in CR than the SR group, and in terms of the mucositis severity, the difference of scale of mucositis was statistically significant on the second day of the experiment in the CR group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Pharmacovigilance is essential for the herbal drug before being considered as a safe for human health [4,5]. For example, our previous reports reveal that cinnamaldehyde, a widely used food additive induces pro-oxidant state and thereby exerting toxic effects at the WHO suggested ADI level [6][7][8][9]. Cinnamaldehyde has been also used as an antidiabetic and also anticancer agent.…”
Section: Vol: 1 Issue:mentioning
confidence: 99%